The Effect of Leadership Style on Psychological Safety of Employees of Maintenance Department of Unit RM 4 & 6 PT Semen Padang - Johanes, Johanes Ganda Sihombing; Rinaldi (Causalita, 2025)
Psychological Safety in the work environment plays an important role because it is closely related to the feeling of security in employees. When someone feels safe in carrying out their work, this can have a positive impact on improving their performance. This study aims to determine the extent to which leadership style influences the level of psychological safety in employees in the Maintenance Department of PT Semen Padang. The study was conducted on the entire population of 35 employees, using a total sampling technique. Data were collected through a scale of measurement of leadership style and psychological safety, and analyzed using a simple regression method. The results showed a positive influence of leadership style on psychological safety of 28.2% (R = 0.531; R Square = 0.282; p <0.05). In general, both the level of leadership style and psychological safety are in the high category. This means that the more positive the leadership style felt by employees, the higher the level of psychological safety they experience in the workplace.